Pengaruh religiusitas terhadap kesejahteraan psikologis dimoderasi oleh dukungan sosial teman sebaya - Situmorang, Khairunnisa Br; Milfayetty, Sri; Hasanuddin, Hasanuddin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
The purpose of this study was to see the effect of religiosity on psychological well-being and to see the role of peer social support in moderating the effect of religiosity on psychological well-being in PAI students at the Daar Al-Uluum Asahan Islamic Institute. The research method uses a quantitative approach. the data collection tools used are religiosity scales, psychoogical well-being and social support of friends as many as 200 samples in this study were obtained by purposive sampling technique. then the data were analyzed by moderate regression analysis. The data were analyzed using the structural equation model (SEM) technique multifariat amos version 23.0. Based on the results of the study, it shows that there is an effect of religiosity on psychological well-being and there is a role of peer social support as moderation in the effect of religiosity on the psychological well-being of PAI students of the Islamic Institute of Religion Daar Al-Uluum Asahan.